Peran Kepala Sekolah Dalam Meningkatkan Etos Kerja Guru di MIN 1 Rembang - Harni; Murdiansyah Indra Putranto; Soedjono (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This research is motivated by the fact that there are still teachers who have not fully carried out their main roles and duties in educating, teaching, guiding, directing, training, assessing and evaluating students properly. The aim of this research is to describe the role of school/madrasah principals in improving the work ethic of teachers at MIN 1 Rembang. The type of research used in this research is a case study. In this research, the subject is the role of the school/madrasah principal at MIN 1 Rembang. Data collection techniques were obtained from documentation, observation and interviews. Data analysis techniques go through the stages of data collection, data reduction, data presentation and conclusion. Based on the research results, it was found that the role of the principal in improving the work ethic of teachers at MIN 1 Rembang is by creating good teamwork by involving teachers in every activity and providing the tagline MIN 1 Rembang Solid, creating discipline, creating a comfortable working atmosphere, providing fair wages. comply with the GTT appropriately and ensure that salaries and certification for civil servants run smoothly every month, as well as establishing good communication between school principals and teachers.